Evolution and Application of Inteins in Candida species: A Review - Fernandes, José A. L.; Prandini, Tâmara H. R.; Castro, Maria da Conceiçao A.; Arantes, Thales D.; Giacobino, Juliana; Bagagli, Eduardo; Theodoro, Raquel C. (Frontiers in Microbiology, 2016)
Inteins are invasive intervening sequences that perform an autocatalytic splicing from their host proteins. Among eukaryotes, these elements are present in many fungal species, including those considered opportunistic or primary pathogens, such as Candida spp. Here we reviewed and updated the list of Candida species containing inteins in the genes VMA, THRRS and GLT1 and pointed out the importance of these elements as molecular markers for molecular epidemiological researches and species-specific diagnosis, since the presence, as well as the size of these inteins, is polymorphic among the different species. Although absent in Candida albicans, these elements are present in different sizes, in some environmental Candida spp. and also in most of the non-albicans Candida spp. considered emergent opportunistic pathogens. Besides, the possible role of these inteins in yeast physiology was also discussed in the light of the recent findings on the importance of these elements as post-translational modulators of gene expression, reinforcing their relevance as alternative therapeutic targets for the treatment of non-albicans Candida infections, because, once the splicing of an intein is inhibited, its host protein, which is usually a housekeeping protein, becomes nonfunctional.